GENDER TYPING (PADA ANAK USIA SEKOLAH DASAR) - Asriana Harahap (Universitas Muhammadiyah Tapanuli Selatan, 2019)
Abstract: The word gender in Indonesian is borrowed from English. When viewed in a dictionary, there is no clear distinction between sex and gender. Meanwhile, there is no explanation that is able to explain briefly and clearly about the concept of gender and why the concept is important to understand the system of social injustice. In other words, the emergence of obscurity is caused by a lack of explanation about the link between the concept of gender and other issues of injustice. Gender is one of the important aspects that influence social development in the early days of children. Gender terms are intended behavior and attitudes associated with men and women. Most children experience at least three stages in gender development. First, children develop beliefs about gender identity, namely the feeling of men or women. Second, children develop gender privileges, attitudes about which sex they want. Third, they obtain gender provisions, a belief that a person's sex is determined biologically, permanently, and does not change. Although everyone basically assumes that the behavior of children as male or female is caused by an interaction of biological factors and environmental factors, one's view of interaction is not the same for everyone. For some people, this view suggests that certain environmental conditions are needed before the trends previously programmed appear. Culture, schools, peers, the media, and other family members are other sources. However, it is important to keep from shifting too far from this direction because especially in the early years of parental development is an important influence on gender development. According to the theory of cognitive development towards gender, the gender forms of children arise after they develop a concept of gender. When they understand themselves as men or women consistently, children often arrange their world according to gender. Keyword: Typing Gender, Sekolah Dasar.